NURSING PROFESSIONALS' COMPLIANCE WITH HAND-WASHING: AN ANALYSIS ACCORDING TO THE HEALTH BELIEF MODEL - Matilde Guedes; Fernanda Moura D'Almeida Miranda; Eliane Cristina Sanches Maziero; Fernanda Leticia Frates Cauduro; Elaine Drehmer de Almeida Cruz (Universidade Federal do Paraná, 2012)
A descriptive and analytic study, whose objective was to understand factors related to the practice of hand-washing. 40 nursing professionals from a teaching hospital in the capital of Paraná participated in the study in the period from April to May 2007. Semi-structured interviews based on the Health Belief Model were undertaken; data analysis was done with the help of descriptive statistics and excerpts from the statements were used to illustrate the opinions and value given to the practice of hand-washing. The majority referred to having participated in training on the theme under study, recognized its importance and their own susceptibility to infections, cited it as a benefit in the prevention of these, and indicated as barriers lack of knowledge and skin problems arising from hand-washing. The Health Belief Model afforded recognition of the local reality and can contribute to the planning of actions aimed at promoting hand-washing.